Pengaruh Faktor Sosial Ekonomi Keluarga Nelayan Terhadap Konsumsi Ikan Di Kecamatan Pasangkayu Kabupaten Mamuju Utara - Rosdiani Rosdiani (Universitas Tadulako, 2015)
This study aimed to find out the characteristics social economic fisherman families in Pasangkayu Subdistrict and analyze the effect of social economic factors (household income, the price of fish, the price of substitute goods, level of education, total of familiy responsibilities and the age of respondens) fisherman families toward fish consumption in Pasangkayu Subdistrict Mamuju Utara Regency. This study conducted in pasangkayu Subdistrict Mamuju Utara Regency West Sulawesi on June-August 2014. The total samples in this study were 74 families, selected by using proportional stratified random sampling method. The obtained data were analyzed using multiple linier regression analysis (SPSS versi 21) and tested with the classical assumption. Descriptif analysis using the average and percentage indicate that social economic factors of fiherman families has a strong category. Research result show that simultaneously social economic factors fisherman families significantly affect on fish consumption in Pasangkayu Subdistrict Mamuju Utara Regency, partially varialbe household income of fisherman families, fish price, chicken price, egg price, age of respondents and total of family responsibilities are significant effect on fish consumption in Pasangkayu Subdistrict Mamuju Utara Regency.